Exploring the Impact of Hyperbolic Figures of Speech Analysis in 'The Greatest Showman' Theme - Nyoman Widhi Wisesa; Komariyah Komariyah; Latifah Latifah (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the impact of hyperbolic figurative analysis in the theme of the film "The Greatest Showman". By paying attention to the use of excessive language in narration and dialogue, this study reveals how hyperbolic figurative enriches the audience's experience and conveys deep messages in the context of the film's theme. By using an analytical approach and case studies from the film, this research provides new insights into the power and significance of hyperbolic figurative in audiovisual works of art.